PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN MENGGUNAKAN DIMENSI PENGUKURAN KAPITALISASI : (Studi Kasus di Bursa Efek Indonesia) - Pratiwi Yani; Mega Arisia Dewi (PROGRAM STUDI AKUNTANSI - UNIVERSITAS MUHAMMADIYAH KUPANG, 2018)
This research discussing about impact of changes in corporate governance implementation oflisted companies in Indonesian Stock Exchange for three consecutive years from 2013 up to 2015refer to survey from independent institution called Indonesian Institute for Corporate Directorship(IICD) to company performance using capitalization measurement of Return on Asset (ROA),stock return and price to book value. The research resulted changes in corporate governanceimplementation in company has no impact to stock return however these changes have an impactin ROA and price to book value. Impact in changes of corporate governance implementation incompanies to ROA and price to book value comes from significant changes. If the changes are notsignificant then it will have no impact to ROA and price to book value of a company. Meanwhileinconsistency result comes from indicators of stock return to ROA and price to book value. Thisresult shows that ROA and price to book value are better indicators compared to stock return sincethose indicators are more case-sensitive to changes in corporate governance implementation incompanies.